Analyzing Online Purchase Intentions in Indonesia: Fashion e-Commerce - Pramuji, Iddo Ahmad; Setyawan, Anton Agus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Technological advances are constantly changing. One of them is technological progress in the field of e-commerce-based businesses, and the rise of e-commerce makes many people less confident in buying products. Therefore, companies need to understand the needs of the online market and provide products that are effective enough to motivate consumers to buy their products. This study aims to determine people's purchase intention when shopping online. This research uses quantitative research methods and the sampling method of this research is non-probability sampling. The data collection method used in this research is the distribution of likert questions. The group of people studied in this study is consumers who are interested in buying fashion through e-commerce number of participants: 150 people. Data analysis technique using his SmartPLS V.3.00 for data processing, this study found that perceived security has a positive and negative impact on trust. Information quality has a positive and significant effect on trust. A sense of security has a positive and negative influence on purchase intentions. Information quality has a significant positive effect on purchase intention. This study helps address the gap created by purchase intentions in online shopping. Particularly for fashion products, the findings require manufacturers to adopt better strategies to increase trust and improve purchase intentions by providing more information. This gives consumers more desire to buy.